Transducer-Like Protein in Campylobacter jejuni With a Role in Mediating Chemotaxis to Iron and Phosphate - Chandrashekhar, Kshipra; Srivastava, Vishal; Hwang, Sunyoung; Jeon, Byeonghwa; Ryu, Sangryeol; Rajashekara, Gireesh (Frontiers in Microbiology, 2018)
Chemotaxis-mediated motility enables Campylobacter jejuni to navigate through complex environmental gradients and colonize diverse niches. C. jejuni is known to possess several methyl accepting chemotaxis proteins (MCPs), also called transducer-like proteins (Tlps). While the role of some of the Tlps in chemotaxis has been identified, their regulation and role in virulence is still not very clear. Here, we investigated the contribution of Tlp2 to C. jejuni chemotaxis, stress survival and colonization of the chicken gastrointestinal tract. The Δtlp2 deletion mutant showed decreased chemotaxis toward aspartate, pyruvate, inorganic phosphate (Pi), and iron (FeSO4). Transcriptional analysis of tlp2 with a promoter fusion reporter assay revealed that the tlp2 promoter (Ptlp2) was induced by Pi and iron, both in the ferrous (Fe2+) and ferric form (Fe3+). RT-PCR analysis using overlapping primers indicated that the phoX gene, located immediately downstream of tlp2, is co-transcribed with tlp2. A transcription start site was identified at 53 bp upstream of the tlp2 start codon. The Δtlp2 mutant showed decreased colonization of the chicken gastrointestinal tract. Collectively, our findings revealed that the tlp2 plays a role in C. jejuni pathogenesis and colonization in the chicken host and its expression is regulated by iron.